High Levels of Physical Activity in Anorexia Nervosa: A Systematic Review. (18th June 2015) - Gümmer, Ricarda; Giel, Katrin Elisabeth; Schag, Kathrin; Resmark, Gaby; Junne, Florian Philipp; Becker, Sandra; Zipfel, Stephan; Teufel, Martin
Abstract High level physical activity is a frequent symptom in patients with anorexia nervosa (AN), influencing the development, maintenance, complications, treatment success, relapse rate and severity of the disease. Accelerometry is assumed to be an objective method to assess physical activity (PA) in AN. We aimed to review objectively measured levels of PA in AN and to give an overview for clinical practice and future research. Data were searched in PubMed and PsychINFO until April 2015 following the preferred reporting items for systematic reviews and meta‐analyses statement. Twenty studies fulfilled the inclusion criteria. A notable heterogeneity of measurements, outcomes, participants and settings was found. Overall, HLPA is not adressed enough by current evidence. A common valid terminology of HLPA is not available, and accurate criteria of different levels of PA must be defined to create comparability of future studies. Further objective PA assessments are needed to improve treatment outcome and relapse rate. Copyright © 2015 John Wiley & Sons, Ltd and Eating Disorders Association.